Medication non-adherence as a cause of hospital admissions - N. Martínez López de Castro; M. Álvarez Payero; M. Ucha Samartín; A. Martín Vila; C. Vázquez López; G. Piñeiro Corrales (Elsevier, 2014)
Objectives: 1. To determine the profile of patients who are admitted to hospital as a result of non-adherence. 2. To obtain an estimate of the economic impact for the hospital. Methods: Observational and retrospective study that included patients who were admitted to hospital with a secondary diagnosis of «Personal history of non-compliance with chronic medication» according to International Classification of Diseases, during 2012. Data collected: demographics; socioeconomic and clinical data; data related to the treatment; readmissions; hospital days; degree of adherence: ≤75% or severe non-adherence and > 75% or moderate non-adherence; type of non-adherence: non-persistence and noncompliance; hospitalization costs. Statistical analysis was performed. Results: Eighty-seven patients were admitted. These patients caused 104 episodes (16.3% were readmissions). 71.2% were men, and 51.5 (SD 17.8) years old. All patients had a chronic disease, adherence ≤75% (76%) and non-persistence (63.5%). Polypharmacy (47.1%) was not associated with non-adherence. Total stay was 1,527 days (mean stay was 14.7 (SD 14.0) days/episode): psychiatry 827 days (54.2%); cardiology 174 days (11.4%); critical unit 48 days (3.1%). Patients with a degree of adherence ≤75% had a mean stay/episode higher than those with a degree of adherence > 75%, without significant differences (p > 0.05, t-Student). Overall cost of hospitalization was 594,230.8, with a mean cost/episode: 5,713.6 (SD 5,039.5). Mean cost/episode for adherence ≤75% was higher than > 75%, 6,275.8 (SD 5,526.2) vs 3,895.6 (SD 2,371.3), (p < 0.05, t-Student). Conclusions: The profile of this patient is fundamentally, a male psychiatric or chronic cardiac patient with a degree of adherence ≤75% due to abandoning domiciliary treatment. Admissions due to medication non-adherence are associated with an important depletion of economic resources in the hospital.